Cardiac Rupture from Blunt Chest Trauma Diagnosed on Transesophageal Echocardiography. (February 2015) - Gerlach, Rebecca; Mark, David; Poologaindran, Anujan; Tanzola, Rob
<x xml:space="preserve">Abstract</x> Supplemental Digital Content is available in the text.